Challenges Faced by Islamic Organizations in Promoting Sustainability: a case study of islamic union student association (Hima Persis) - Surizkika, Aldi; Haq, Ihsan Abdul (PT Mattawang Mediatama Solution, 2025)
This study examines the challenges faced by the Islamic Unity Student Association (HIMA PERSIS) in promoting sustainability and intellectual development within Islamic organizations in Indonesia. The research employs qualitative methodology through literature study analysis of primary sources about HIMA PERSIS and secondary sources about related organizations. The results reveal four major challenges: the dichotomy between religious and worldly knowledge, contradictions between service and cadre welfare in research activities, internal feudalism as a crisis obstacle, and the impact of stigma and stereotypes on collaboration and innovation. The findings suggest that HIMA PERSIS faces significant organizational coordination issues, resource limitations, and struggles in balancing traditional Islamic values with modern academic demands, while its implementation of the ulul albab concept remains underdeveloped within the organization's framework. Keywords: ; Hima Persis; sustainability; organizational challenges; Islamic education; intellectual development